Adolescents’ Application of the Virtues Across Five Cultural Contexts - Thoma, Stephen; Walker, David; Chen, Yen-Hsin; Frichand, Ana; Moulin-Stożek, Daniel; Kristjansson, Кristjan (American Psychological Association, 2019)
Little is known about adolescent applications of the virtues such as honesty, responsibility and courage across different cultural contexts. Using the Adolescent Intermediate Concepts Measure we analyze samples of adolescents (ages 12 to 20; N 9,112) from 5 contexts: North Macedonia, Mexico, Taiwan, the United Kingdom, and the United States. Across samples, adolescents provide evidence of developmental growth in the ability to apply virtue concepts as assessed by responses to dilemma-based situations. Within these trends, participants found it easier to identify action choices that reflect the virtue concepts as compared to justifications for possible actions. Additionally, participants were better able to identify appropriate applications of the virtues as compared to inappropriate ones. Gender differences favoring females were noted across samples. Overall, similarities across settings were more striking than differences suggesting that there is value in viewing the virtues as a normative component of character development across the adolescent years.
Keywords: virtues, moral development, culture